2022
DOI: 10.1111/bcp.15358
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐human study of eliapixant (BAY 1817080), a highly selective P2X3 receptor antagonist: Tolerability, safety and pharmacokinetics

Abstract: Aims Neuronal hypersensitisation due to adenosine triphosphate‐dependent P2X3 receptor signalling plays a significant role in several disorders including chronic cough and endometriosis. This first‐in‐human study of eliapixant (BAY 1817080) investigated the tolerability, safety and pharmacokinetics (PK) of single doses of eliapixant, including the effect of food and coadministration with a CYP3A inhibitor on eliapixant relative bioavailability. Methods In this randomised, double‐blind phase I study (NCT0281710… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…the lower baseline cough counts and efficacy results in the 150 mg eliapixant group. The safety and tolerability profiles in PAGANINI are generally consistent with other studies of eliapixant in healthy subjects and the phase 2a study in patients with RCC [16][17][18]. However, a case of a moderate DILI of hepatocellular origin occurred during treatment with 150 mg eliapixant and contributed to the need for intensified liver monitoring in clinical trials with eliapixant.…”
Section: B)supporting
confidence: 75%
See 1 more Smart Citation
“…the lower baseline cough counts and efficacy results in the 150 mg eliapixant group. The safety and tolerability profiles in PAGANINI are generally consistent with other studies of eliapixant in healthy subjects and the phase 2a study in patients with RCC [16][17][18]. However, a case of a moderate DILI of hepatocellular origin occurred during treatment with 150 mg eliapixant and contributed to the need for intensified liver monitoring in clinical trials with eliapixant.…”
Section: B)supporting
confidence: 75%
“…Eliapixant is a potent P2X3 receptor antagonist with a good tolerability profile in healthy subjects, and high selectivity over the P2X2/3 receptor in vitro, potentially resulting in fewer off-target effects [15][16][17]. In a phase 2a study, eliapixant significantly reduced cough frequency and severity in patients with RCC, with a lower rate of taste-related side effects than those observed with therapeutic doses of gefapixant [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, sivopixant was shown to reduce objective cough frequency and improved health-related quality of life, with a low incidence of taste disturbance, among patients with a refractory or unexplained chronic cough in a phase 2a trial (Niimi et al, 2022). Eliapixant showed favorable tolerability with no taste-related adverse events in its first-in-human study, and in a phase 1/2a study, eliapixant administration showed reduced cough frequency and severity and was well-tolerated with acceptable rates of taste-related events (Morice et al, 2014;Klein et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The eliapixant 150 mg BID dose was chosen based on previous studies in healthy volunteers, which used a different formulation to that used in PUCCINI, where a 750 mg dose was approximately equivalent to the 150 mg dose used in PUCCINI for bioavailability. 23,28 In healthy volunteers, the eliapixant plasma levels predicted to achieve $80% P2X3 receptor occupancy, the predicted therapeutic threshold, were reached with doses of 200 mg and 750 mg BID. 23 In a phase 2a study assessing eliapixant 50, 200, and 750 mg BID (the same formulation as used in the healthy volunteer studies) in patients with RCC, an efficacy plateau appeared to be reached at 200 mg BID for the primary endpoint of cough frequency, whereas the subjective endpoints continued to improve at the 750 mg dose.…”
Section: Aes N (%)mentioning
confidence: 99%